A postfunctionalist theory of multilevel governance. (November 2020) - Hooghe, Liesbet; Marks, Gary
Multilevel governance describes the diffusion of authority away from the central state. In this contribution, we recount how an archaic term, governance, became part of the vocabulary of political science. We then outline three building blocks of a postfunctionalist theory of multilevel governance. The first is that multilevel governance is cooperation to provide collective goods at diverse scales. The second is that the form governance takes depends on the sociality of the participants. The third is that conflict over community enables or impedes multilevel governance.